Extracts of different pollen species and their effect on human tear fluid and an epithelial cell line. (2nd January 2019) - Rabensteiner, Dieter Franz; Rabensteiner, Jasmin; Horwath-Winter, Jutta; Lang-Loidolt, Doris; Wedrich, Andreas; Heidinger, Andrea; Schwantzer, Gerold; Schmut, Otto
Abstract: Purpose: Hazelnut and birch pollen are known to destroy tear film components and attack ocular surface cells. We investigated further pollen species from different plant families, whether they show similar effects on human tear fluid and an epithelial cell line in vitro, to provide a broad basis for further research on pollen reactions affecting the tear film and ocular surface. Materials and methods: Regional pollen species from different plant families (Adoxaceae, Betulaceae, Fagaceae, Juglandaceae, Malvaceae, Oleaceae, Pinaceae, Plantaginaceae, Poaceae, Salicaceae, Sapindaceae) were collected. Their proteolytic activity was evaluated by Zymography. Human tear fluid and cells of an epithelial cell line were incubated with pollen extracts. Tear fluid was analyzed by Polyacrylamide gel electrophoresis (PAGE). Cytomorphology was assessed microscopically and cell viability by proliferation (MTS), water-soluble tetrazolium (WST-1) assay and the impedance-based xCELLigence real-time analysis (RTCA). Results: Zymography revealed significant protease activity and PAGE showed the degradation of tear proteins by different pollen species. Cells incubated with pollen extracts presented dose- and time-dependent cytomorphological changes. MTS, WST-1, and RTCA revealed cytostatic as well as cytotoxic effects of pollen extracts. Conclusions: Pollen species from different plant families exert proteolytic activity and degrade human tear fluid as well as epithelial cells, which may play a crucial role in the pathogenesis of allergic and non-allergic reactions affecting the ocular surface.